Epibulbar Choristoma, Dermolipoma: Poster Presentation - Case Report - General practitioner - Maykel Sondak; Samuel Samatara (Majalah Oftalmologi Indonesia, 2023)
Introduction : Choriostoma is a tissue anomalie distinguished by distinct cell types that are not typically present at the affected region. Dermolipoma is one type of choriostoma. Case Illustration : A twenty three year old woman is presented with epibulbar mass in the left eye since birth. She wished to remove the mass for cosmetic purposes. She denied any underlying medical condition and ocular history. Her visual acuity was 6/6 in both eyes and intraocular pressure was normal. Slit lamp examination revealed a yellowish white lesion of the external canthus of the left eye, no redness, and no discharge. The mass was 5 x 10 mm. Fundus examination was unremarkable. Patient underwent mass excision with cosmetic indication and has a satisfactory result. Discussion : A dermolipoma is an epibulbar choriostoma made of thick connective tissue and adipose tissue. The benign tumor is rare and makes up 4.2% of all conjunctival lesions. Dermolipoma can be very large, involving the extraocular muscle, lacriminal gland, and orbital tissue. Dermolipoma may be connected to epidermal nevus syndromes, Goldenhar syndrome, or coloboma. The majority of the time, these tumors don't need to be treated unless they are larger or have an unfavorable appearance. Conclusion : Dermolipoma is not cosmetically acceptable may be treated with excision of the mass.